Pengolahan Belimbing Wuluh (Averrhoa Bilimbi L.) terhadap Daya Terima Manisan sebagai Makanan Selingan Penderita Hiperkolesterol - Ririn Yuni Asfita; Rijanti Abdurrachim; Desya Medinasari Fathullah (Jurnal Kesehatan Indonesia, 2022)
Starfruit is a Malay name for a type of fruit from the Oxalidaceae family, Averrahoa clan. Candied fruit is a fruit preserved with sugar. Flavonoids play a role in preventing the risk of heart disease, saponins can reduce serum cholesterol levels, vitamin c (ascorbic acid) as an antioxidant. This study aimed to determine the acceptability of candied starfruit (Averrhoa bilimbi L.) as a snack for people with hypercholesterolemia. The specific objective was to identify the respondent's acceptance (color, aroma, taste) of the sweet starfruit Averrhoa bilimbi L.) as a snack for people with hypercholesterolemia. The method used was pure experimental with a completely randomized design research. The research was conducted to determine the acceptability of the sweet starfruit (Averrahoa bilimbi L.) organoleptic results, namely assessment and observing color, aroma, taste. Organoleptic testing was a way of assessing the five senses, and thereby it can be concluded that the acceptability contained in sweets included color, taste, aroma, namely: The highest color on P3 was 3,1 with the criteria of liking. The highest taste in P3 was 3,1 with like criteria. The highest aroma in P3 was 3,2 with like criteria. Acceptance of color, aroma, and taste of sweets were proven to have differences with different treatments with probability values of 0,000<α respectively at the 95% confidence level (α=0,05).